INVESTIGATION OF UNEMPLOYMENT ANXIETY OF UNIVERSITY STUDENTS FROM THE PERSPECTIVE OF BEHAVIORAL ECONOMICS (Third Sector Social Economic Review, 2022)
This study aims to examine the concept of unemployment in terms of behavioral economics. Mixed research design was used in this study. A sequential quantitative-qualitative technique was used in the research. The sample for the quantitative research consists of 835 students studying in different departments at Iğdır University, Samsun University and Ondokuz Mayıs University. In the text analysis on whether university students experience unemployment anxiety, it was seen that unemployment anxiety was emphasized and it was associated with today's conditions. When the solution proposals of university students are examined, it is seen that there are suggestions such as training each person according to their own abilities and wishes, the decrease in foreign dependency and opening of factories, focusing on competition-oriented growth, encouraging the tourism sector, not showing unfair favor, having employers who will not think that our education is insufficient, providing language education, ensuring education equality, reducing the gap in income distribution, reducing the salary gap
Keywords: Behavioral Economics; Youth Unemployment; Unemployment Anxiety